Budaya Politik Sivil dan Pendemokrasian di Indonesia : Sebuah Analisa Politik - Fauzan, Indra; Sulaiman, Nidzam (Universitas Medan Area, 2019)
Democratization in Indonesia is a political shift from non-democracy to democracy. This political shift affects political change in Indonesia. Many scholars see that this democratization is due to the factors of economic recession, internal internal conflicts and political parties of New Order advocates, Student Movements or opposition. The aim of this study is to see how the process of political culture in Indonesia has come to the democratization of many scholars who have overlooked this political culture. The method used is literature study in the context of collecting data through documents such as Books, Journals, Bachelor Theses and some other references, this method of inquiry is chosen to better understand the political condition of Indonesia textually. In this context, political culture has become a major factor in the catalysts of democratization because the political culture of a middle-class society is a result of a long process resulting in the formation of civil values that impede democratization. This article ultimately aims to contribute thought in the process of building democratic values during democratization.